2018
DOI: 10.1155/2018/6957497
|View full text |Cite
|
Sign up to set email alerts
|

c‐Met Signaling Protects from Nonalcoholic Steatohepatitis‐ (NASH‐) Induced Fibrosis in Different Liver Cell Types

Abstract: Nonalcoholic steatohepatitis (NASH) is the most common chronic, progressive liver disease in Western countries. The significance of cellular interactions of the HGF/c-Met axis in different liver cell subtypes and its relation to the oxidative stress response remains unclear so far. Hence, the present study is aimed at investigating the role of c-Met and the interaction with the oxidative stress response during NASH development in mice and humans. Conditional c-Met knockout (KO) lines (LysCre for Kupffer cells/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…Although the mechanism by which CARCs develop remains unknown, studies have speculated the involvement of abnormal lipid metabolism with inflammation in certain cells or tissues based on the pathological findings in our case. A previous study revealed that mice lacking MET proto-oncogene (MET) exhibited severe fatty liver degeneration with increased inflammation of immune cells, causing nonalcoholic steatohepatitis [18]. Evidence suggests that MET inhibition by crizotinib might generate CARCs, although it is difficult to rule out the ability of other MET inhibitors to cause CARC-like complications in clinical studies.…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…Although the mechanism by which CARCs develop remains unknown, studies have speculated the involvement of abnormal lipid metabolism with inflammation in certain cells or tissues based on the pathological findings in our case. A previous study revealed that mice lacking MET proto-oncogene (MET) exhibited severe fatty liver degeneration with increased inflammation of immune cells, causing nonalcoholic steatohepatitis [18]. Evidence suggests that MET inhibition by crizotinib might generate CARCs, although it is difficult to rule out the ability of other MET inhibitors to cause CARC-like complications in clinical studies.…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…MSP/HGFL and HGF both function to promote liver differentiation, regeneration, and tissue repair. Both Ron and the closely-related Met receptor are protective in hepatic fibrosis [ 36 , 103 , 104 , 105 , 106 ]. Recombinant HGF, the ligand for Met, suppressed the progression in a mouse model of NASH, and MSP negatively regulated inflammation and lipogenesis in ex vivo models of NASH [ 54 , 106 , 107 ].…”
Section: Discussionmentioning
confidence: 99%
“…Both Ron and the closely-related Met receptor are protective in hepatic fibrosis [ 36 , 103 , 104 , 105 , 106 ]. Recombinant HGF, the ligand for Met, suppressed the progression in a mouse model of NASH, and MSP negatively regulated inflammation and lipogenesis in ex vivo models of NASH [ 54 , 106 , 107 ]. Ron and Met primarily signal through the large adaptor protein, Gab1 and loss of Gab1 has been shown to aggravate experimental liver fibrosis in mice [ 108 , 109 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is of great significance to identify new and effective strategies for the treatment of liver fibrosis. There is increasing evidence indicates that several cell types are involved in the development of liver fibrosis (29,30). However, activation of HSCs is a central process in the pathogenesis of liver fibrosis (4), and the activation of HSCs is mediated by a variety of inflammatory factors and growth factors (5).…”
Section: Discussionmentioning
confidence: 99%